2013
DOI: 10.1007/s00405-013-2396-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cochlear implantation on quality of life in the elderly

Abstract: The purpose of this study was to evaluate the benefits of unilateral cochlear implant (CI) in patients over 60 on speech perception and quality of life, comparing the results obtained with a control group of younger CI recipients. Twenty CI users (mean age 72 years), postlingually deafened, were included in this study. Audiological performance was evaluated using bisyllabic words and sentences recognition tests in a quiet and a noise environment. Moreover, we administered two questionnaires to evaluate the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
22
1
2
Order By: Relevance
“…Overall, implanted older adults showed significant improvement in QoL after implantation [Chung et al, 2012;Di Nardo et al, 2014;Olze et al, 2012;Orabi et al, 2006;Ramos et al, 2013;Vermeire et al, 2005]. Improvements in QoL were independent of audiological performance.…”
Section: Summary Of Results For Older Adultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Overall, implanted older adults showed significant improvement in QoL after implantation [Chung et al, 2012;Di Nardo et al, 2014;Olze et al, 2012;Orabi et al, 2006;Ramos et al, 2013;Vermeire et al, 2005]. Improvements in QoL were independent of audiological performance.…”
Section: Summary Of Results For Older Adultsmentioning
confidence: 79%
“…Improvements in QoL were independent of audiological performance. While all studies demonstrated significant auditory benefit of CI in all age groups, some studies [Di Nardo et al, 2014;Ramos et al, 2013;Vermeire et al, 2005] showed poorer auditory performance in the elderly group, and others showed a similar benefit of CI regardless of age [Olze et al, 2012;Orabi et al, 2006]. Regardless, nearly all studies showed significant improvement in QoL in this age group, most often reported in multiple dimensions.…”
Section: Summary Of Results For Older Adultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study evaluating the QOL in post-lingual adults and elderly users of cochlear implant through the SF-36 and "Questionnaire for Self-Assessment of CI Benefit" questionnaires observed a significant increase in QOL subdomains and total score (23) . The comparison of the quality of life results with the EG and CG pointed out similar results between groups, with a significant difference only for the domain 4 (environment).…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some different responses to the questionnaire between groups, both showed very good result and satisfaction with CI. Results obtained in terms of auditory perception, general health and perceived benefit showed that advanced chronological age could not be considered as major factor limiting the effectiveness of CI [32].…”
Section: Discussionmentioning
confidence: 94%